The potential usefulness of standardized assessments to measure participant outcomes of adaptive/therapeutic horseback riding: a survey study - Hanson, Moriah R.; Alm, Kathy; Fields, Beth; Gabriels, Robin; Schmid, Arlene A.; Stallones, Lorann; Peters, B. Caitlin (Frontiers in Veterinary Science, 2023)
Adaptive or therapeutic riding (A/TR) is a recreational activity which provides mounted and groundbased horsemanship opportunities adapted to the abilities of the participants. A/TR provides physical and psychological benefits to participants with diverse disabilities, including physical, developmental, cognitive, and age-related disabilities, promoting higher quality of life. A/TR professionals may be limited in their capacity to implement outcome assessments and report the benefits of their community-based A/TR services to a broad audience. The purpose of this study was to identify whether and how A/TR professionals currently measure participant outcomes; benefits and barriers to implementing standardized assessments in A/TR; and characteristics which would make assessments useful in the community-based A/TR environment. To address this purpose, we conducted a survey among A/TR professionals. We found that while A/TR professionals measure outcomes among their participants, they typically do not use standardized assessments. Survey respondents believed benefits of implementing standardized assessments included bolstering the A/TR profession, acquiring funding, and communicating about A/TR services to a broad audience. Respondents also identified several barriers to implementing standardized assessments including time, systemic, and expertise constraints. Respondents reported that useful standardized assessments would be relevant to all age groups and populations who receive A/TR services. Finally, respondents shared that for standardized assessments to be useful, they would need to be low-cost, require less than 10-20 minutes, and available in either paper or computer format. This study revealed that standardized assessments may be a strong support to the A/TR profession; however, assessments must meet the unique needs of A/TR professionals.